Dukungan Orangtua terhadap Pendidikan Seksual pada Anak Retardasi Mental : Narative Review - Hendrawati Hendrawati; Liesna Fitriani; Iceu Amira; Ema Arum; Indra Maulana (Malahayati Nursing Journal, 2024)
ABSTRACT It is important to give sexual education to every child, including children with mental retardation, because they will grow and develop. Parental support is also important in providing sexual education because they are someone who interacts with the child every day. This literature study aims to determine parental support for sexual education for children with mental retardation. This research uses a narrative review method with data based on PubMed, EBSCO and Google Scholar. Search for literature using the keywords Support, Parents, Sexual Education, Mental Retardation / Intellectual Disability / Mental Retardation /Learning Disability/Developmental Disability / Learning Disabilities. Articles were synthesized according to the inclusion criteria: Original research, full text articles, in addition articles regarding parental support for sexual education for children with mental retardation were taken as samples, the year of publication of the article was a maximum of the last 10 years (2011-2020), used English or Indonesian, article regarding parental support for sexual education for mentally retarded children. 67,670 articles were found, after analysis. 8 articles were found, which revealed that parents had not received and understood how to overcome the problem of providing sexual education at home. Parental support regarding sex education for children with mental retardation is very much needed and must be done early to prevent abuse. sexual education so it is important to provide psychoeducation to parents to increase children's knowledge regarding sexual education. Key words: Parental support, sexual education, mental retardatioABSTRAK Pendahuluan: Pendidikan seksual penting diberikan pada setiap anak termasuk anak  dengan retardasi mental karena mereka akan tumbuh dan berkembang. Dukungan  orangtua juga penting dalam memberikan pendidikan seksual karena mereka  merupakan seseorang yang berinteraksi dengan anak tersebut setiap hari. Studi  literatur ini bertujuan untuk mengetahui dukungan orangtua terhadap pendidikan  seksual pada anak retardasi mental. Metode: Penelitian ini menggunakan metode narrative review dengan data based  PubMed, EBSCO dan googleScholer. Pencarian litratur dengan menggunakan kata kunci Dukungan / Support, Orangtua / Parent, Pendidikan Seksual / SexEducation, Retardasi Mental/Tunagrahita/Intellectual Disability/Mental Retardation / Learning Disability / Developmental Disability /Learning Disabilities. Artikel disentesis sesuai dengan kriteria inklusi: Penelitian original, artikel  full teks, sebagai tambahan artikel mengenai dukungan orangtua terhadap  pendidikan seksual pada anak retardasi mental diambil sebagai sampel, tahun  terbit artikel maksimal 10 tahun terakhir (2011-2020), menggunakan bahasa  Inggris atau Indonesia, artikel mengenai dukungan orangtua terhadap pendidikan  seksual pada anak retardasi mental. 67.670 artikel ditemukan,setelah dianalisis. Didapatkan 8 artikel, yang mengungkapkan  bahwa  orangtua belum mendapatkan dan memahami  cara mengatasi masalah pemberian pendidikan seksual di rumah. Dukungan orang tua tentang pendidikan seks pada anak Retardasi mental sangat dibutuhkan dan harus dilakukan secara dini untuk mencegah terjadinya pelecehan seksual sehingga   psikoedukasi  penting diberikan kepada  orangtua guna meningkatkan pengetahuan anak mengenai  pendidikan seksual. Kata kunci: Dukungan orangtua, Pendidikan seksual, Retardasi  Mental